CAPE-pNO2 Inhibited the Growth and Metastasis of Triple-Negative Breast Cancer via the EGFR/STAT3/Akt/E-Cadherin Signaling Pathway - Huang, Qin; Li, Sai; Zhang, Liwen; Qiao, Xufang; Zhang, Yanyan; Zhao, Xiaoyan; Xiao, Guojun; Li, Zhubo (Frontiers in Oncology, 2019)
Overexpressed epidermal growth factor receptor (EGFR) and overactivated epithelial-mesenchymal transition (EMT) in triple-negative breast cancer (TNBC) can enhance tumorigenesis and tumor recurrence and metastasis. Caffeic acid p-nitro-phenethyl ester (CAPE-pNO2) has various pharmacological activities in our previous research, but its effect on metastasis and growth of TNBC has not been studied. In this study, Caffeic acid phenethyl ester (CAPE) was as a positive control. In vitro, MTT, Transwell, wound healing, colony formation and cell adhesion assays were performed to examine the effect on viability, invasion, migration, colony formation and adhesion of MDA-MB-231 cells by CAPE-pNO2, the results indicated that CAPE-pNO2 significantly dose-dependently inhibited metastasis of MDA-MB-231 cells (p<0.05). In vivo, TNBC xenograft mice were established by subcutaneously injected with MDA-MB-231 cells, and they were used to estimate the effect on metastasis and growth of CAPE-pNO2 after 38 days of treatment. HE staining and TUNEL staining were carried out in tumor tissues, results showed that CAPE-pNO2 obviously suppressed the tumor growth, induced cells apoptosis (p<0.01) and decreased pulmonary and splenic metastatic tumor cells. The results of IHC demonstrated that the VEGFA and Ki-67 proteins expression were downregulated (p<0.01) in tumor tissues. Furthermore, western blot analysis was used to quantify key metastasis- and growth-associated proteins expression in vitro and in vivo, the results suggested that CAPE-pNO2 downregulated the proteins expression of p-EGFR, p-STAT3, p-Akt, MMP-2, MMP-9, Survivin and key EMT-related proteins (Vimentin and N-cadherin) (p<0.01), and increased the expression of E-cadherin (p<0.01) in vivo and in vitro. Besides, CAPE-pNO2 had a similar effect as erlotinib in regulating the EGFR downstream proteins in EGF-induced MDA-MB-231cells. Collectively, these results indicated that CAPE-pNO2 possessed inhibitory effect on the growth and metastasis of TNBC may via the EGFR/STAT3/Akt/E-cadherin signaling pathway, and CAPE-pNO2 is better than CAPE in inhibiting growth and metastasis.